Karol Wojtyła’s Concept of Personal Transcendence - Gudaniec, Arkadiusz (Verbum Vitae, 2022)
The article presents the understanding of the transcendence of the person in Wojtyła’s philosophy. The text discusses in turn: the role of the experience of the person; the concept of transcendence in relation to other concepts used by Wojtyła; the reference to the truth as the basis of personal transcendence; the integration of the person; the transcendence in the personal existence. The analyses conducted in the article show that transcendence of the person in the proper sense reveals the spiritual dimension of his existence as being superior to the material dimension. The presented text draws attention to the richness of threads showing the transcendence of the person in action on the basis of an analysis of lived experience. This approach not only illuminates or presents from another side the traditional concept of transcendence, based on the essential distinction between person and nature, but also adds new and revealing aspects to it. The person as an autonomous subjectivity not only freely determines himself/herself, but moreover transcends humanity as a general human nature – in virtue of an individual, unique personal existence. As a crowning achievement of the concept of the transcendence of the person, the metaphysical aspect of anthropology, which is strongly present in Wojtyła’s thought, is proposed here, which is somewhat new in the treatment of the topic of transcendence. According to this approach, transcendence experienced in action reveals its deeper level: transcendence in existence, which reveals the deepest foundation of being a person.